I alle sine dager. Mette-Marits heltemodige hypergami - Døving, Runar (Tidsskrift for kulturforskning, 2006)
We live in a society with a clear ideology of equality, at the same time as which we recognize that "everybody's different" and we marry people from the same social stratum supported by the saying "birds of a feather flock together". In this context, a young female commoner with an unconventional background marries the monarchy's Crown Prince. She is transformed to a princess. The article demonstrates how the popular press and discourses use princess fairytales as analogies to her real life, and in so doing, mix structural mythemes in a complex relationship between fable and reality. In such a structural analysis of Mette-Marit's hypergamy, she is construed entirely as a representation. The article shows which problems arise when one marries above oneself; or rather, which problems arise in a stratified society when dealing with the ascribed status in a marriage that bestows privileges. Mette-Marit's marriage was accordingly regarded as strategic, as female guile. The article also interprets her marriage as a culturally therapeutic exercise where the ideology of equality is confirmed, at the same time as which disparities are safeguarded. In this structural context, the main participant is doomed to fail.